Measurement of the natural radioactivity in building materials used in Ankara and assessment of external doses - Turhan, Şeref; Baykan, U.N.; Şen, K (JOURNAL OF RADIOLOGICAL PROTECTION, 2008)
A total of 183 samples of 20 different commonly used structural and covering building materials were collected from housing and other building construction sites and from suppliers in Ankara to measure the natural radioactivity due to the presence of 226Ra, 232Th and 40K. The measurements were carried out using gamma-ray spectrometry with two HPGe detectors. The specific activities of the different building materials studied varied from 0.5 ± 0.1 to 144.9 ± 4.9 Bq kg−1, 0.6 ± 0.2 to 169.9 ± 6.6 Bq kg−1 and 2.0 ± 0.1 to 1792.3 ± 60.8 Bq kg−1 for 226Ra, 232Th and 40K, respectively. The results show that the lowest mean values of the specific activity of 226Ra, 232Th and 40K are 0.8 ± 0.5, 0.9 ± 0.4 and 4.1 ± 1.4 Bq kg−1, respectively, measured in travertine tile while the highest mean values of the specific activity of the same radionuclides are 78.5±18.1 (ceramic wall tile), 77.4±53.0 (granite tile) and 923.4 ± 161.0 (white brick), respectively. The radium equivalent activity (Raeq), the gamma-index, the indoor absorbed dose rate and the corresponding annual effective dose were evaluated to assess the potential radiological hazard associated with these building materials. The mean values of the gamma-index and the estimated annual effective dose due to external gamma radiation inside the room for structural building materials ranged from 0.15 to 0.89 and 0.2 to 1.1 mSv, respectively. Applying criteria recently recommended for building materials in the literature, four materials meet the exemption annual dose criterion of 0.3 mSv, five materials meet the annual dose limit of 1 mSv and only one material slightly exceeds this limit. The mean values of the gammaindex for all building materials were lower than the upper limit of 1.